Diversidade de formigas (Hymenoptera: formicidae) de fragmentos florestais em Santa Maria, Rio Grande do Sul, Brasil - Ribeiro, Taíse Colpo (2011)
Ants belong to a hyperdiverse social insect group with many species used as ecological indicators of their habitat conditions. This study aims to analyze richness, species composition, diversity, evenness, and environmental variables associated to leaf-litter ant fauna of eight forest fragments in the municipality of Santa Maria, Central Depression region of Rio Grande do Sul State, Brazil. The sampling followed standard protocol through a 200-m transect placement by fragment. In order to proceed statistical analyses, the fragments were grouped in two categories, according to their conservation status, preserved or on regeneration. Eighty ant species belonging to 24 genera and nine subfamilies were registered. Myrmicinae, Formicinae and Ponerinae, and Camponotus, Hypoponera and Pheidole were respectively the richest subfamilies and genera and Solenopsis sp. 1 and Gnamptogenys striatula were the most frequent species. Shannon-Wiener and Margalef diversity indexes had the same ordination among fragments, highest at FRJB 01, and lower at FRCE 05. The dominance indexes had the same ordination among higher values but differed among lower ones. FRJB 01 for Simpson and FPMC 06 for Berger-Parker. The fragments separation on two distinct groups was showed by NMDS and confirmed by similarity analyses. The dissimilarity percentage analysis showed that Gnamptogenys striatula and Wasmannia sp. 3 had the highest contribution for conservation status differentiation. The preserved fragments had more similarity among each other than the regeneration ones, highlighting Gnamptogenys striatula and Solenopsis sp. 1 at the first group, and Solenopsis sp. 1 and Hypoponera sp. 4 at the other. Only edge effect showed relationship with species richness among all environmental variables measured. Based on results, the studied ant fauna communities showed noticeably richness and composition partially related to their habitat traits. Although, other factors as adjacent vegetational areas isolation, regeneration time and history and intensity of disturbances could be interfering on these communities structure and their associated biodiversity.